Exploring Multicultural Education: A Case Study of Singkawang - Buwono, Sri; Queiroz, Carla; Karolina, Venny; Xaixanith, Toby (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This article investigates multicultural education in Singkawang, Indonesia, where diverse ethnicities coexist. Rapid social changes often trigger ethnic migration, leading to a convergence of cultures. Ethnocentrism can impede inter-ethnic communication, fostering stereotypes and ethnic conflicts. Multicultural education, emphasizing democratic, humanistic, and pluralistic values, is proposed to address these issues. Singkawang, recognized for its ethnic diversity, serves as a unique case study. The research method involves qualitative analysis with interviews from students, teachers, and parents from various ethnic backgrounds. Findings revealed the city's friendly atmosphere, preserved harmony, and respectful behavior, especially among students.